Determining the influence exerted by the static conditions of final squeezing on the compaction process of iron-based powder materials - Minitsky , Anatoly; Minitska, Nataliya; Okhrimenko , Oleksandr; Krasnovyd , Dmytro (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into the process of re-compaction of powder briquettes in the conditions of static pressing at a pressure of 800 MPa. The technological parameters of the pressing process have been analyzed, which make it possible to improve the compaction of powder briquettes based on iron. Such parameters are the outer greasing, which reduces friction between a green compact and the walls of the press tool matrix, and the firing, which removes the deformation strengthening of the green compacts and increases their plasticity. The green compacts’ sealing mechanism involved in the final squeezing process has been established, which is associated with the grinding of pre-compressed particles due to the strain in the contact areas. The increase in the stressed state of green compacts following the final squeezing was confirmed by the results of studying the residual micro-strains. The change in the stressed state of iron green compacts has been confirmed by the study into the structurally sensitive characteristics, which include the materials’ magnetic and electrical properties. Determining the magnetic characteristics has shown that final squeezing leads to an increase in coercive force, which can be explained by both the increase in the stressed state and the grinding of grains. Investigating the impact exerted by the annealing environment on the value of magnetic characteristics has demonstrated that annealing in hydrogen is more effective in terms of improving magnetic properties than annealing in a vacuum. This is due to the refining of grain boundaries through the processes of reduction of oxide films. The study of the mechanical characteristics of green compact materials based on iron powder has established that final squeezing leads to an increase in the hardness and strength of materials depending on the conditions of deformation. A significant improvement in the green compacts’ strength (820‒824 MPa) is due to both a decrease in porosity by 8‒10 % and an increase in the contact area as a result of plastic deformation after the annealing